ANTIOXIDANT AND LIPID PEROXIDANTION INHIBITORY OF COMPOUNDS IN COMMON BUCKWHEAT - Neamah, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Common Buckwheat (Fagopyrum esculentum Moench) is recognized as a healthy food in many countries because it is nutrient-rich crop. The objectives of this study was to investigate the succesful farming for buckwheat plants in the Iraqi environmental conditions, extraction and estimation of the most important nutritional and medicinal compounds from seeds plant and it᾽s effectiveness in the inhibition of lipids peroxidation which considered to be the causative agent of the free radicals formation in vivo.The hexane and methanolic extraction gave many compounds from buckwheat seeds. NMR were used to determine many of the natural compounds for buckwheat plants seeds after many steps of the purification processes, using many solutions and mobile phases including: Linoleic acid, Triglyceride, Stearic acid, Ferulic acid, Flavonoid glycoside and Flavon glycoside. Compounds Linolieic acid, Ferulic acid, Flavonoid glycoside and Flavon glycoside showed activity values of 0.285, 0.362, 0.356 and 0.442 respectively at 250 µg/mL concentration in the MTT assay and inhibited LPO by 58, 73, 93 and 76% respectively at 250 µg/mL concentration. It is clear that buckwheat have strong antioxidant and lipid Peroxidation inhibitory. nd